2016
DOI: 10.1111/mmi.13452
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial SRP receptor, FtsY, is activated on binding to the translocon

Abstract: SummaryProteins are inserted into the bacterial plasma membrane cotranslationally after translating ribosomes are targeted to the translocon in the membrane via the signal recognition particle (SRP) pathway. The targeting pathway involves an interaction between SRP and the SRP receptor, FtsY. Here we focus on the role of FtsY and its interaction with the translocon in controlling targeting. We show that in unbound FtsY the NG and A domains interact with one another. The interaction involves the membrane-target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 63 publications
2
46
0
Order By: Relevance
“…Although in this area the secondary structure elements are not resolved, we assigned this density to the SR A-domain since previous studies showed that the A-domain binds to both the membrane and the translocon232442434445. Furthermore, such a positioning of the A-domain between the translocon and the NG domain of the SR is consistent with recent biochemical results, which indicate that the translocon activates the receptor by binding to the A-domain and separating it from the NG domain27.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Although in this area the secondary structure elements are not resolved, we assigned this density to the SR A-domain since previous studies showed that the A-domain binds to both the membrane and the translocon232442434445. Furthermore, such a positioning of the A-domain between the translocon and the NG domain of the SR is consistent with recent biochemical results, which indicate that the translocon activates the receptor by binding to the A-domain and separating it from the NG domain27.…”
Section: Resultssupporting
confidence: 78%
“…According to this model, the translocon is initially recruited to the targeting complex via hydrophobic and electrostatic interactions with the intrinsically disordered A-domain of SR232427. However, in spite of its central importance in the SRP cycle, such a quaternary complex has never been visualized and it is currently not understood how the final events of this process are spatially and temporally orchestrated.…”
mentioning
confidence: 99%
“…Figure 5B vs. Figure 5C). Thus, additional auto-inhibitory interactions, presumably from the remainder of the N-domain (Neher et al, 2008; Draycheva et al, 2016), are present to prevent free FtsY-NG+1 from engaging with the membrane in the Stable mode (Figure 5F and G, red lines from N-domain). Finally, protein targeting efficiency paralleled the restoration of the Stable mode in free FtsY across the A-domain truncation mutants (Figure 6C and D), consistent with the Stable mode being an obligatory species during targeting.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple observations suggest that lipid interaction of αN1 removes it from these auto-inhibitory contacts and thus primes FtsY for complex formation with SRP: (i) αN1 was proteolytically cleaved in all the crystal structures of closed SRP•FtsY complexes (Shepotinovskaya and Freymann, 2002; Gawronski-Salerno and Freymann, 2007; Shepotinovskaya et al, 2003; Egea et al, 2004; Focia et al, 2004); (ii) EPR studies showed that formation of the closed complex with SRP leads to significant mobilization of the αN1 helix, suggesting that it is released from the remainder of FtsY (Lam et al, 2010); (iii) consistent with the prediction from (ii), closed complex formation with SRP substantially increases the binding of FtsY to liposomes (Lam et al, 2010; Parlitz et al, 2007); and (iv) an FtsY-dN1 mutant, in which αN1 is deleted, is superactive in GTPase activity and in stable complex formation with SRP (Neher et al, 2008), phenocopying the stimulatory effect of lipids on FtsY. Together with the finding that lipids are also required for the interaction of FtsY with the SecYEG translocon (Kuhn et al, 2015), these observations led to the current model in which most FtsY molecules are membrane-bound through the αN1 helix and pre-activated for receiving cargo-loaded SRP (Kuhn et al, 2015; Parlitz et al, 2007; Lam et al, 2010; Draycheva et al, 2016; Braig et al, 2011) (Figure 1, lower pathway in blue ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation